A method for preparing size-adjustable magnetic gel microspheres

By generating magnetic particles Fe3O4 by generating a magnetic granules in the middle position in the methadal alginate gel micro -ball, and the second ion cross -linking, the problem of unprecedented and stability of the magnetic gel micro -balls was solved, and the magnetic gel was realized. The size of the microsphere can be evenly distributed with magnetic nanoparticles, which improves magnetic response, controllability and stability.

CN118755109BActive Publication Date: 2025-01-21YANGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410978449.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2025-01-21
Estimated Expiration
2044-07-22

AI Technical Summary

Technical Problem

In the prior art, the size of magnetic gel microspheres is uncontrollable, the magnetic nanoparticles are prone to accumulate, and the stability is poor, which affects the magnetic response and controllability.

Method used

By preparing methacrylated sodium alginate gel microspheres and generating magnetic particles Fe3O4 in situ on the gel structure, secondary ion cross-linking is performed through washing with calcium chloride solution to strengthen the microsphere structure and achieve a size that can be achieved. The purpose of adjusting and uniformly distributing magnetic nanoparticles.

Benefits of technology

The size of the magnetic gel microspheres is adjustable, the magnetic nanoparticles are evenly dispersed, the magnetic response and controllability are good, the mechanical properties and stability are also improved, and it is suitable for applications in the biomedical field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118755109B_ABST
    Figure CN118755109B_ABST
Patent Text Reader

Abstract

The invention relates to a method for preparing size-adjustable magnetic gel microspheres. The method comprises the following steps: adding methacrylic anhydride to a sodium alginate solution, reacting under alkaline conditions, dialyzing, and dissolving after freeze drying to obtain a methacrylated sodium alginate gel solution; mixing the methacrylated sodium alginate gel solution with a surfactant and an oil phase, stirring, adding a calcium chloride solution, stirring to obtain an oil emulsion, removing the oil phase to obtain a deoiled emulsion, sieving to obtain methacrylated sodium alginate gel microspheres; firstly adding the methacrylated sodium alginate gel microspheres to a metal ion soaking solution for soaking, then adding the methacrylated sodium alginate gel microspheres to a basic soaking solution for soaking, and finally adding the methacrylated sodium alginate gel microspheres to a calcium chloride solution for soaking, filtering, washing, and drying to obtain magnetic gel microspheres. The magnetic gel microspheres prepared by the method have uniformly dispersed magnetic nanoparticles, can perform certain magnetic drive migration under the action of an external magnetic field, have good magnetic response and controllability, have good mechanical properties, and have good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano composite hydrogels, and in particular to a method for preparing magnetic gel microspheres with adjustable sizes. Background Art

[0002] Hydrogels are three-dimensional network polymers composed of hydrophilic polymer chains. These three-dimensional cross-linked hydrophilic networks are particularly suitable for the biomedical field due to their good biocompatibility and properties similar to human tissues. They can be used as highly absorbent materials, soft scaffolds that simulate the extracellular matrix environment, and media for drug storage and delivery.

[0003] Magnetic hydrogels have the characteristics of remote operation, rapid response and easy control due to their unique magnetic response. Currently, most preparation methods are to introduce magnetic nanoparticles (MNPs) or other organic ferromagnets into the hydrogel matrix, which plays an important role in magnetic resonance imaging, magnetocaloric effect, drug delivery and other aspects, but the preparation methods of magnetic micron-scale gel microspheres are rarely described in detail.

[0004] In the prior art, the common method for preparing magnetic hydrogels is a blending method, which is to first synthesize magnetic nanoparticles, then mix them with hydrogel precursors, and finally polymerize them into hydrogels. This method is simple, but magnetic nanoparticles are prone to agglomeration and leakage in the solution environment. Agglomeration of magnetic nanoparticles may cause magnetic inhomogeneity, which may affect the overall magnetic response and controllability of the hydrogel, reduce mechanical properties, and deteriorate stability, which will affect applications such as drug transportation and magnetic separation. Summary of the invention

[0005] The invention aims to solve the technical problems in the prior art that the size of magnetic gel microspheres is uncontrollable, magnetic nanoparticles are easy to accumulate and the stability is poor, and provides a method for preparing magnetic gel microspheres with adjustable microsphere size, uniform distribution of magnetic nanoparticles and good stability.

[0006] The object of the present invention is achieved by a method for preparing size-adjustable magnetic gel microspheres, comprising the following steps:

[0007] (1) preparing a methacrylic sodium alginate gel solution: adding methacrylic anhydride to a sodium alginate solution to obtain a cross-linking reaction solution, adjusting the temperature of the cross-linking reaction solution, stirring the solution under alkaline conditions to allow the solution to react sufficiently, dialyzing the solution, and freeze-drying the solution to obtain a methacrylic sodium alginate xerogel, dissolving the methacrylic sodium alginate xerogel, and preparing a methacrylic sodium alginate gel solution for standby use;

[0008] (2) Preparing methacrylated sodium alginate gel microspheres: pouring the methacrylated sodium alginate gel solution prepared in step (1) into a beaker containing a surfactant and an oil phase, stirring evenly, adding a calcium chloride solution, stirring to obtain an oil emulsion, removing the oil phase in the oil emulsion to obtain a deoiled emulsion, sieving, and obtaining methacrylated sodium alginate gel microspheres;

[0009] (3) Preparing metal ion-loaded gel microspheres: adding the methacrylated sodium alginate gel microspheres prepared in step (2) into a metal ion soaking solution to obtain metal ion-loaded gel microspheres;

[0010] (4) preparing gel microspheres carrying magnetic nanoparticles: adding the metal ion-carrying gel microspheres prepared in step (3) into an alkaline soaking solution to obtain gel microspheres carrying magnetic nanoparticles;

[0011] (5) Preparation of magnetic gel microspheres: The gel microspheres loaded with magnetic nanoparticles prepared in step (4) are added to a calcium chloride solution and soaked. After sufficient reaction, the solution is filtered, washed, and dried to obtain magnetic gel microspheres.

[0012] Furthermore, step (1) specifically includes the following sub-steps:

[0013] (1.1) Sodium alginate and pure water are fully mixed to prepare a sodium alginate solution with a concentration of 0.5-5% w / v, and an appropriate amount of methacrylic anhydride is slowly added dropwise to the sodium alginate solution to obtain a cross-linking reaction solution. The cross-linking reaction solution is protected from light and continuously stirred at 400 r / min for 24 h at a temperature of 0-5°C. During the entire stirring process, the pH of the cross-linking reaction solution is maintained at 8-9. After sufficient reaction, a cross-linking reaction product is obtained;

[0014] (1.2) placing the cross-linking reaction product obtained in step (1.1) into a dialysis bag with a molecular weight cutoff of 12 to 14 kDa, changing the water at least once a day, and continuing the dialysis for one week, and freeze-drying the bag in a freeze dryer to obtain a methacrylylated sodium alginate xerogel;

[0015] (1.3) Dissolve the methacrylated sodium alginate dry gel prepared in step (1.2) in an aqueous solution containing a photoinitiator I2959 at a concentration of 0.5% w / v to prepare a methacrylated sodium alginate gel solution at a concentration of 1 to 10% w / v for standby use.

[0016] Furthermore, step (2) specifically includes the following sub-steps:

[0017] (2.1) Pour the methacrylated sodium alginate gel solution prepared in step (1.3) into a mixed solution containing a surfactant and an oil phase, stir at a speed of 300 to 550 r / min until uniform, add a calcium chloride solution with a concentration of 0.8 to 1.5% w / v, and continue stirring to obtain an oil emulsion;

[0018] (2.2) pouring the oily emulsion prepared in step (2.1) into anhydrous ethanol for washing to remove the oil phase, thereby obtaining a deoiled emulsion;

[0019] (2.3) The deoiled emulsion obtained in step (2.2) is sieved through a 70-200 mesh sieve to obtain methacrylated sodium alginate gel microspheres.

[0020] Furthermore, step (5) specifically includes the following sub-steps:

[0021] (5.1) adding the magnetic nanoparticle gel microspheres prepared in step (4) into a 0.5-5% w / v calcium chloride solution and soaking for 5-10 minutes to allow for sufficient reaction to obtain a secondary crosslinking solution;

[0022] (5.2) The secondary cross-linked liquid obtained in step (5.1) is centrifuged to filter the waste liquid, and then washed alternately with deionized water and anhydrous ethanol until the pH value is about 7, and vacuum dried to obtain magnetic gel microspheres.

[0023] Furthermore, in step (1.1), the volume ratio of the methacrylic anhydride to the sodium alginate solution is (1-6):50, and the methacrylic anhydride is slowly added dropwise to the sodium alginate solution at a rate of 0.5 mL / min to 1 mL / min.

[0024] Furthermore, in step (2.1), the oil phase is one of peanut oil, olive oil and soybean oil.

[0025] Furthermore, in step (2.1), the surfactant is Span 80, and the volume ratio of Span 80 to the oil phase is 1:50; the volume ratio of the methacrylated sodium alginate gel solution, the oil phase mixed with Span 80, and the calcium chloride solution is (1-3):5:(0.5-1).

[0026] Further in step (3), the metal ion soaking solution is a mixed solution of FeCl3·6H2O, FeSO4·7H2O and deoxygenated deionized water, the molar ratio of FeCl3·6H2O to FeSO4·7H2O is 1:2, and the concentration of FeCl3 in the mixed solution is 2-6% w / v, and the concentration of FeSO4 is 1-3% w / v.

[0027] Furthermore, in step (4), the alkaline soaking solution is a sodium hydroxide solution with a concentration of 1 to 20% w / v, and the soaking time in the alkaline soaking solution is 10 to 40 minutes.

[0028] Furthermore, the vacuum drying conditions are as follows: vacuum degree 100-200 Pa, temperature 20-50° C., and time 12 h-24 h.

[0029] The present invention utilizes methacrylic anhydride to modify sodium alginate so that it has both ionic crosslinking and photocrosslinking function. The crosslinked and cured methacrylic sodium alginate gel is used as a reaction container to react with divalent iron and trivalent iron to generate magnetic particles Fe3O4 in situ on the gel structure. Due to the invasion of metal particles, part of the calcium ions are replaced, accompanied by the generation of ferroferric oxide, which may cause part of the sodium alginate chain segments to dissociate. The secondary ionic crosslinking is performed by washing with a calcium chloride solution to strengthen the microsphere structure and achieve a secondary curing effect. The dispersibility of Fe3O4 in the gel is improved. The magnetic gel has good properties and the shape of the prepared magnetic gel is not limited. The present invention can prepare gel microspheres (referred to as magnetic gel microspheres) with different sizes of magnetic nanoparticles according to different needs through an emulsion method and sieving assistance. The structure size is adjustable. The magnetic gel microspheres prepared by the present invention have uniform dispersion of magnetic nanoparticles in the magnetic gel microspheres, can undergo certain magnetic-driven migration under the action of an external magnetic field, have good magnetic response and controllability, have good mechanical properties, and have good stability. Tissue scaffold materials for different application scenarios can be constructed through an external magnetic field and magnetic gel microspheres, and can be applied to the biomedical field. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a scanning electron microscope image of the magnetic gel microspheres prepared in Example 1 of the present invention.

[0031] Figure 2 This is a scanning electron micrograph of the gel microspheres prepared in the comparative example of the present invention without undergoing magnetic modification.

[0032] Figure 3 This is the hysteresis loop of the magnetic gel microspheres in Example 1 of the present invention.

[0033] Figure 4 These are optical images of magnetic gel microspheres of different sizes in Example 2 of the present invention. DETAILED DESCRIPTION

[0034] The present invention is further analyzed, explained and compared by means of specific embodiments and comparative examples.

[0035] Example 1

[0036] (1) Heat 2 g of sodium alginate powder to dissolve in 50°C, 200 mL of deionized water, and stir at 450 r / min for 60 min to fully dissolve. Adjust the temperature to 0-5°C. After the system is stable, slowly add 12 mL of methacrylic anhydride for 20 min to obtain a cross-linking reaction solution. Protect the cross-linking reaction solution from light and stir at 400 r / min for 24 h at a temperature of 0-5°C. During the whole stirring process, keep the pH of the cross-linking reaction solution at 8 to fully react and obtain a cross-linking reaction product. Put the cross-linking reaction product into a dialysis bag with a molecular weight cutoff of 12-14 kDa, change the water twice a day, and continue dialysis for one week. Place it in a freeze dryer for freeze drying to obtain methacrylic sodium alginate xerogel, dissolve it in an aqueous solution of photoinitiator I2959 with a concentration of 0.5% w / v, and prepare a methacrylic sodium alginate gel solution with a concentration of 4% w / v for standby use.

[0037] (2) Pour the methacrylated sodium alginate solution prepared in step (1) into the oil phase mixed with Span surfactant Span 80 at a ratio of 2:5, with the oil phase accounting for about 25 mL, and the beaker is selected to be 80 mL. Adjust the speed to 350 r / min, wait until the system is stable, add about 4 mL of 1.2% w / v calcium chloride solution, continue stirring, and obtain the oil emulsion, pour it into a 500 mL beaker containing 200 mL of anhydrous ethanol, and pour it while stirring. Remove the oil phase by washing with anhydrous ethanol to obtain a deoiled emulsion, first pass the deoiled emulsion through a 70-mesh sieve to obtain the filtrate, and then pass the filtrate through a 120-mesh sieve to obtain the retentate, which is the prepared methacrylated sodium alginate gel microspheres, and set aside;

[0038] (3) FeCl3·6H2O and FeSO4·7H2O were mixed and dissolved in deoxygenated deionized water at a molar ratio of about 2:1 to prepare solutions with concentrations of 5.6% w / v and 2.8% w / v, and the gel microspheres prepared in step (2) were poured into the prepared metal ion solution and soaked for 6 h; taken out and rinsed with anhydrous ethanol to obtain metal ion-loaded gel microspheres;

[0039] (4) Then, the metal ion-loaded gel microspheres prepared in step (3) are placed in a 16% w / v sodium hydroxide solution and soaked for 15 min; taken out to obtain gel microspheres loaded with magnetic nanoparticles;

[0040] (5) The gel microspheres loaded with magnetic nanoparticles prepared in step (4) are first soaked in a calcium chloride solution for 5 min to effect secondary cross-linking, and then washed alternately with deionized water and anhydrous ethanol until the pH of the washing solution is about 7; and placed in a vacuum dryer at 35° C. for 18 h to obtain gel microspheres loaded with magnetic nanoparticles (referred to as magnetic gel microspheres).

[0041] Example 2

[0042] (1) Heat 2 g of sodium alginate powder and dissolve it in 200 mL of deionized water at 50°C. Stir at 450 r / min for 30 min to fully dissolve it. Adjust the temperature to 0-5°C. After the system is stable, slowly add 10 mL of methacrylic anhydride for 15 min to obtain a cross-linking reaction solution. Protect the cross-linking reaction solution from light, and use sodium hydroxide solution to adjust the pH of the cross-linking reaction solution (system) to 8. Keep the system temperature at 0-5°C and stir at 400 r / min for 24 h. After sufficient reaction, obtain a cross-linking reaction product. Put the cross-linking reaction product into a dialysis bag with a molecular weight cutoff of 12-14 kDa, change the water twice a day, and continue dialysis for one week. Place it in a freeze dryer for freeze drying to obtain methacrylic sodium alginate xerogel, dissolve it in deionized water containing 0.5% w / v I2959, and prepare a methacrylic sodium alginate gel solution with a concentration of 6% w / v for standby use.

[0043] (2) Pour the methacrylated sodium alginate solution prepared in step (1) into the oil phase mixed with the surfactant at a ratio of 3:5, with the oil phase accounting for about 30 mL and the beaker being 80 mL. Adjust the speed to 400 r / min, wait until the system is stable, drop about 5 mL of 0.8% w / v calcium chloride solution, continue stirring, and obtain the oil emulsion, pour it into a 500 mL beaker containing 200 mL of anhydrous ethanol, stir while pouring, remove the oil phase by washing with anhydrous ethanol, and obtain the deoiled emulsion, first pass the deoiled emulsion through a 120-mesh sieve to obtain the filtrate, and then pass the filtrate through a 200-mesh sieve to obtain the retentate, which is the prepared methacrylated sodium alginate gel microspheres, and set aside;

[0044] (3) FeCl3·6H2O and FeSO4·7H2O are mixed and dissolved in deoxygenated deionized water at a molar ratio of about 2:1 to prepare a 5% w / v ferric chloride solution and a 2.5% w / v ferrous sulfate solution. The gel microspheres prepared in step (2) are poured into the prepared metal ion solution and soaked for 10 h; taken out and rinsed with anhydrous ethanol to obtain metal ion-loaded gel microspheres;

[0045] (4) Then, the gel microspheres were immersed in a 15% w / v sodium hydroxide solution for 20 min. The gel microspheres were taken out to obtain the magnetic nanoparticle-loaded gel microspheres.

[0046] (5) The magnetic nanoparticle-loaded gel microspheres prepared in step (4) are first soaked in a calcium chloride solution for 5 min to effect secondary cross-linking, and then washed alternately with deionized water and anhydrous ethanol until the pH of the washing solution is about 7; and then placed in a vacuum dryer at 40° C. for 12 h to obtain magnetic gel microspheres.

[0047] Example 3

[0048] (1) 3 g of sodium alginate powder was heated and dissolved in 50°C, 200 mL of deionized water, and magnetically stirred at 450 r / min for 30 min to fully dissolve. The temperature was adjusted to 0-5°C. After the system was stable, 20 mL of methacrylic anhydride was slowly added dropwise for 30 min to obtain a cross-linking reaction solution. The cross-linking reaction solution was protected from light and stirred continuously at 400 r / min for 24 h at a temperature of 0-5°C. During the whole stirring process, the pH of the cross-linking reaction solution was maintained at 8. After sufficient reaction, a cross-linking reaction product was obtained. The cross-linking reaction product was loaded into a dialysis bag with a molecular weight cutoff of 12-14 kDa, and the water was changed twice a day. Dialysis was continued for one week, and the product was placed in a freeze dryer for freeze drying to obtain methacryloyl sodium alginate xerogel, which was dissolved in deionized water containing 0.5% w / v I2959 to prepare a methacryloyl sodium alginate gel solution with a concentration of 5% w / v for standby use.

[0049] (2) Pour the methacryloylated sodium alginate solution prepared in step 1 into the oil phase mixed with the surfactant at a ratio of 1:3, with the oil phase accounting for about 30 mL and the beaker being 80 mL. Adjust the speed to 450 r / min, wait until the system is stable, drop about 4 mL of 1.5% w / v calcium chloride solution, continue stirring, and obtain the oil emulsion, pour it into a 500 mL beaker containing 200 mL of anhydrous ethanol, and pour it while stirring. Remove the oil phase by washing with anhydrous ethanol to obtain the deoiled emulsion, first pass the deoiled emulsion through a 120-mesh sieve to obtain the filtrate, and then pass the filtrate through a 200-mesh sieve to obtain the retentate, which is the prepared methacryloylated sodium alginate gel microspheres, and set aside;

[0050] (3) FeCl3·6H2O and FeSO4·7H2O were mixed in a molar ratio of about 2:1 and dissolved in deoxygenated deionized water to prepare solutions with concentrations of 4% w / v and 2% w / v. The gel microspheres prepared in 2 were poured into the prepared metal ion solution and soaked for 12 h. The microspheres were taken out and rinsed with anhydrous ethanol to obtain metal ion-loaded gel microspheres.

[0051] (4) Then, the gel microspheres were immersed in a 12% w / v sodium hydroxide solution for 30 min and taken out to obtain gel microspheres loaded with magnetic nanoparticles;

[0052] (5) The prepared magnetic nanoparticle-loaded gel microspheres were first soaked in a calcium chloride solution for 5 min to effect secondary cross-linking, and then washed alternately with deionized water and anhydrous ethanol until the pH of the washing solution was about 7; the microspheres were placed in a vacuum drying oven and vacuum dried at 30°C for 24 h to obtain magnetic gel microspheres.

[0053] Comparative Example

[0054] The difference between this comparative example and Example 1 is that the methacrylated sodium alginate gel microspheres prepared in step (2) are vacuum dried at 30° C. for 12 h to obtain gel microspheres that are not magnetically modified.

[0055] The magnetic gel microspheres prepared in Example 1 and the non-magnetically modified gel microspheres prepared in the comparative example were characterized by scanning electron microscopy and recorded as Figure 1 and Figure 2 .

[0056] Figure 1 The scanning electron microscope image of the magnetic gel microspheres prepared in Example 1 shows that the size of the magnetic gel microspheres is about 100 um. The surface of the microspheres is locally magnified by scanning electron microscopy, and it is found that the surface is covered with lamellar magnetic nanoparticles. Many nanoscale particles are generated on the surface of the magnetically modified gel microspheres, indicating that the magnetic particles are successfully loaded on the gel microspheres.

[0057] Figure 2 The scanning electron microscope image of the gel microspheres prepared in the comparative example without magnetic modification shows that the size of the microspheres is about 100 um. By locally enlarging the surface of the microspheres, Figure 1 contrast, Figure 2 The surface of the microspheres is relatively smooth, without lamellar particle loading.

[0058] Figure 3 The magnetic gel microspheres prepared in Example 1 were subjected to hysteresis loop analysis by a vibrating sample magnetometer. Under a magnetic field strength of 20,000 Oe, the specific magnetization intensity of the magnetic gel microspheres was above 2.5 emu / g, meeting the basic requirements of magnetic drive braking.

[0059] Figure 4 a is an optical image of the magnetic gel microspheres (particle size is about 0-100 um) prepared in Example 2, and Figure 4 b) compared with the magnetic gel microspheres in Example 1 (particle size is about 100-200 um). By comparing 4a and 4b, it can be observed that both have uniform macroscopic magnetic attraction, but the magnetic properties of small-sized magnetic gel microspheres (such as Figure 4 a) The magnetic attraction phenomenon is more obvious.

Claims

1. A method for preparing size-adjustable magnetic gel microspheres, comprising the following steps: (1) preparing a methacrylic sodium alginate gel solution: adding methacrylic anhydride to a sodium alginate solution to obtain a cross-linking reaction solution, adjusting the temperature of the cross-linking reaction solution, stirring the solution under alkaline conditions to allow the solution to react sufficiently, dialyzing the solution, and freeze-drying the solution to obtain a methacrylic sodium alginate xerogel, dissolving the methacrylic sodium alginate xerogel, and preparing a methacrylic sodium alginate gel solution for standby use; (2) Preparing methacrylated sodium alginate gel microspheres: pouring the methacrylated sodium alginate gel solution prepared in step (1) into a beaker containing a surfactant and an oil phase, stirring evenly, adding a calcium chloride solution, stirring to obtain an oil emulsion, removing the oil phase in the oil emulsion to obtain a deoiled emulsion, sieving, and obtaining methacrylated sodium alginate gel microspheres; (3) Preparing metal ion-loaded gel microspheres: adding the methacrylated sodium alginate gel microspheres prepared in step (2) into a metal ion soaking solution to obtain metal ion-loaded gel microspheres; (4) preparing gel microspheres carrying magnetic nanoparticles: adding the metal ion-carrying gel microspheres prepared in step (3) into an alkaline soaking solution to obtain gel microspheres carrying magnetic nanoparticles; (5) Preparation of magnetic gel microspheres: The gel microspheres loaded with magnetic nanoparticles prepared in step (4) are added to a calcium chloride solution and soaked. After sufficient reaction, the solution is filtered, washed, and dried to obtain magnetic gel microspheres.

2. The method for preparing size-adjustable magnetic gel microspheres according to claim 1, characterized in that: Step (1) specifically includes the following steps: (1.1) Sodium alginate and pure water are fully mixed to prepare a sodium alginate solution with a concentration of 0.5-5% w / v, and an appropriate amount of methacrylic anhydride is slowly added dropwise to the sodium alginate solution to obtain a cross-linking reaction solution. The cross-linking reaction solution is protected from light and continuously stirred at 400 r / min for 24 h at a temperature of 0-5°C. During the entire stirring process, the pH of the cross-linking reaction solution is maintained at 8-9. After sufficient reaction, a cross-linking reaction product is obtained; (1.2) placing the cross-linking reaction product obtained in step (1.1) into a dialysis bag with a molecular weight cutoff of 12 to 14 kDa, changing the water at least once a day, and continuing the dialysis for one week, and freeze-drying the bag in a freeze dryer to obtain a methacrylylated sodium alginate xerogel; (1.3) Dissolve the methacrylated sodium alginate dry gel prepared in step (1.2) in an aqueous solution containing a photoinitiator I2959 at a concentration of 0.5% w / v to prepare a methacrylated sodium alginate gel solution at a concentration of 1 to 10% w / v for standby use.

3. The method for preparing size-adjustable magnetic gel microspheres according to claim 2, characterized in that: Step (2) specifically includes the following steps: (2.1) Pour the methacrylated sodium alginate gel solution prepared in step (1.3) into a mixed solution containing a surfactant and an oil phase, stir at a speed of 300 to 550 r / min until uniform, add a calcium chloride solution with a concentration of 0.8 to 1.5% w / v, and continue stirring to obtain an oil emulsion; (2.2) pouring the oily emulsion prepared in step (2.1) into anhydrous ethanol for washing to remove the oil phase, thereby obtaining a deoiled emulsion; (2.3) The deoiled emulsion obtained in step (2.2) is sieved through a 70-200 mesh sieve to obtain methacrylated sodium alginate gel microspheres.

4. The method for preparing size-adjustable magnetic gel microspheres according to claim 1, characterized in that: Step (5) specifically includes the following steps: (5.1) adding the magnetic nanoparticle gel microspheres prepared in step (4) into a 0.5-5% w / v calcium chloride solution and soaking for 5-10 minutes to allow for sufficient reaction to obtain a secondary crosslinking solution; (5.2) The secondary cross-linked liquid obtained in step (5.1) is centrifuged to filter the waste liquid, and then washed alternately with deionized water and anhydrous ethanol until the pH is 7, and vacuum dried to obtain magnetic gel microspheres.

5. The method for preparing size-adjustable magnetic gel microspheres according to claim 2, characterized in that: In step (1.1), the volume ratio of the methacrylic anhydride to the sodium alginate solution is (1-6):50, and the methacrylic anhydride is slowly added dropwise to the sodium alginate solution at a rate of 0.5 mL / min to 1 mL / min.

6. The method for preparing size-adjustable magnetic gel microspheres according to claim 3, characterized in that: In step (2.1), the oil phase is one of peanut oil, olive oil and soybean oil.

7. The method for preparing size-adjustable magnetic gel microspheres according to claim 3, characterized in that: In step (2.1), the surfactant is Span 80, and the volume ratio of Span 80 to the oil phase is 1:50; the volume ratio of the methacrylated sodium alginate gel solution, the oil phase mixed with Span 80, and the calcium chloride solution is (1-3):5:(0.5-1).

8. The method for preparing size-adjustable magnetic gel microspheres according to claim 7, characterized in that: In step (3), the metal ion soaking solution is a mixed solution of FeCl3·6H2O, FeSO4·7H2O and deoxygenated deionized water, the molar ratio of FeCl3·6H2O to FeSO4·7H2O is 1:2, and the concentration of FeCl3 in the mixed solution is 2-6% w / v, and the concentration of FeSO4 is 1-3% w / v.

9. The method for preparing size-adjustable magnetic gel microspheres according to claim 8, characterized in that: In step (4), the alkaline soaking solution is a sodium hydroxide solution with a concentration of 1 to 20% w / v, and the soaking time in the alkaline soaking solution is 10 to 40 minutes.

10. The method for preparing size-adjustable magnetic gel microspheres according to claim 4, characterized in that: The vacuum drying conditions are as follows: vacuum degree 100-200 Pa, temperature 20-50° C., and time 12 h-24 h.

Citation Information

Patent Citations

  • Preparation method of ferric oxide nanoparticle supported sodium alginate nanogel

    CN104606687A

  • Magnetic hydrogel as well as preparation method and application thereof

    CN114404665A